The Influence of Function Words on Oral Proficiency Among First Semester EFL Students at the University of Benghazi - Intesar Elwerfalli; Hana Mahmoud; Amal Mohammed (المجلة الأفروآسيوية للبحث العلمي, 2024)
Speaking English properly is a sign of a good mastery of English. Some grammatical elements in English are frequently encountered, yet, they might be difficult to master and apply. Consequently, they hinder students‟ speech flow and affect their speaking accuracy. The main aim of this study was to investigate this problem of frequent function words use in speaking in terms of three-dimensional questions: What, how, and why questions. In other words, this study tried to find what the most frequent function words in students‟ oral production were, and it described how these function words occurred in students‟ speech alongside giving possible reasons for why some frequent function words were used in some occasions of students‟ oral production. Students‟ samples of oral speech were collected using interviews; then their speech was recorded, transcribed, and analyzed. The research findings indicated that the most frequently used function word among students was the subject pronoun "I," while the least used was "you." The usage of function words fell into three categories: correct use, hesitation use, and misuse. Notably, "I" was the most correctly used function word, whereas "you" was the least correctly used. In terms of hesitation, "I" was again the most frequently used, while "it" was the least. The definite article "the" was identified as the most misused function word, with "you" being the least misused. The study concluded that to help learners improve their oral production of function words, these should be taught in communicative contexts using varied teaching methods. Additionally, teachers should be aware of their students' linguistic levels when introducing function words.